Elite athlete development: A medal and event analysis of top performing nations in the Summer Olympic Games. - Mayer, K. C.; Stotlar, D. K. (Asian Sports Management Review, 2016)
The objective of this study was to analyze the success of countries at the Summer Olympic Games, particularly in terms of events and medals. Results of top performing nations (Australia, China, France, Germany, Italy, Russia, South Korea, Ukraine, and the United States) were examined from 1996 through 2012. The one-way ANOVA determined there were significant mean differences in the total medals won by country, in which China, Russia, and the United States performed better than the others. Also, the factor analyses indicated there are specific events that countries were successful comparatively to other top nations. The United States experienced success in the events of Athletics, Basketball, Beach Volleyball, Swimming, and Tennis across all genders, and Gymnastics Artistic in the women`s events. China was successful in Table Tennis, Weightlifting, Shooting, and Badminton across both genders, and Gymnastics Artistic in the men`s events. Russia performed well across both genders in the event of Boxing. The successes of the other nations were also explored, as well as the event areas where no counties were successful. Overall, this study has provided empirical evidence to support sporting success over the past five Olympiads not just as a country, but also the specific event area(s) of that country`s success. This research could impact the way countries distribute their sport resources, along with the route countries utilize to attain Olympic success.